A study of hadhramis communication strategy among local political economy in Aceh - Khairina Abdurrahman, Zulham Ibrahim, Teuku Alfiady, Ristati M. Yahya, Sutriani Sumedi,; Desky, Harjoni; Saputra, Jumadil (Opción, 2019)
The purpose of this paper is to discover the Hadhramis communication strategy from the local perspective, and to analyze the Hadhramis involvement on the local political economy in Aceh, Indonesia. This quantitative study utilized the theory of political communication, communication strategy, and political participation. As a result, the Hadhramis’ communication strategy in Aceh is not strong enough. In conclusion, the communication strategy of the Arab descendant of Aceh is interwoven through the organizations created by them.